Analisis Sistem Pengedalian Intern Penerimaan Kas Pada PT. Mangir Raya - Ivana Nina Esterlin Barus3, Fetti Kholifah1 Eddy Soegiarto2 (EKONOMIA, 2021)
The porpose of thuspaper is to know the internal control system cash receipts at PT. Mangir Raya is in accordance with the elements of the internal control system that has been Â Â Â Â Â established. In accordance with the purpose of this study, the subjek metter raised â€œIs the internal control system cash receipts at PT. Mangir Raya is in accordance with the elements of the internal control system that has been establishedâ€.Â Â Â Â Â Â Â Â Â The basic theory used this research is the internal control system cash receipts at PT. Mangir Raya. Based on the main issues, the hypothesis is proposed as follows : â€œInternal control system cash receipts at PT. Mangir Raya not in accordance with the elements of the internal control system that has been establishedâ€.Â Â Â Â Â Â Â Â Â The analytical tool used in this study is spread of questionnaries and the use of flowchart according to theory.Â Â Â Â Â Â Â Â Â Based on the results of the analyzes previously mentioned, can be seen that the implementation of internal control system cash receipts at PT. Mangir Raya has been running quite well this is evidenced by the result of analysis that received relative value of I 76 % in the cash receipts registrar is said to be â€œvery appropriateâ€. Although it still provides the possibility for certain parties in the company to perform acts of irregularities. The system implemented by the company still has weakness.